The Congress of Micronesia Development of the Legislative Process in the Trust Territory of the Pacific Islands - Meller, Norman (University of Hawai'i Press, 1969)
In the western Pacific Ocean north of the equator, the far-flung islands of Micronesia extend across an area as large as that of the United States. Most of this area is administered by the United States as a trusteeship granted by the United Nations after World War II. Having been governed in turn by three other world powers- Spain, Germany, and Japan- the 91,000 Micronesian inhabitants are now at last in the process of working out their own political future. This book, a thorough, scholarly study of the development of the legislative process in the Trust Territory, focuses on the Congress of Micronesia, the legislature destined to carry the burden of the political development in the Territory. It examines institution-building over a period of two decades, describing how American forms and processes have been modified to fit the indigenous cultures of Micronesia, and how these cultures have accommodated to them. It also treats the impact of institutional change upon the role of indigenous leadership, highlighting the emergence of Micronesian leaders most capable of participating in the new political system. Here are detailed the day by day negotiations to set up a district legislature between the spokesmen for aboriginal Yap (of stone money fame) and the chiefs of the island empire which once paid it tribute. Here is described what happens when the U.S. Supreme Court's "one man, one vote" formula is applied to people yet learning how to vote. The United States today has no defined policy for the eventual status of her Pacific island possessions. The future of Guam and American Samoa remains unclear. But the legislators of the Trust Territory have acted for the people they represent. Their adopted legislative institution will be central in determining whether or not the Trust Territory will become fully self-governing and independent.